2014
DOI: 10.1016/j.ijhydene.2014.06.105
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped graphene with enhanced oxygen reduction activity produced by pyrolysis of graphene functionalized with imidazole derivatives

Abstract: Direct methanol fuel cells (DMFC) are great candidates for portable power source applications. However, the sluggish reaction kinetics are key challenges in DMFC technology. The state-of-the-art electrocatalysts are Pt-based catalysts supported on carbon black. However, the high price of Pt, corrosion of carbon support and Pt degradation are the main problems.In this thesis, carbon nanomaterials, namely few-walled carbon nanotubes (FWCNTs) and graphitized nanofibers (GNFs) were used as catalyst supports in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 149 publications
0
10
0
1
Order By: Relevance
“…Compared with CVD, thermal annealing is a simple, low-cost method with high graphene yield [8]. In addition, NG with specific N configurations can be produced by controlling the annealing temperature [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with CVD, thermal annealing is a simple, low-cost method with high graphene yield [8]. In addition, NG with specific N configurations can be produced by controlling the annealing temperature [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This electron pair increases the electron-donor property of the catalyst, weakening the OeO bond via bonding between oxygen and nitrogen and/or an adjacent carbon atom and facilitating the reduction of O 2 [17,18]. Other studies have claimed that pyridinic-N and graphitic-N play equally important roles in ORR performance [3,9,13,19]. Lai et al [13] observed that graphitic-N greatly increased the limiting current density of NG samples, whereas pyridinic-N species converted the ORR reaction mechanism from a 2-electron dominated process to a 4-electron dominated process.…”
Section: Introductionmentioning
confidence: 99%
“…Впервые N-легированный графен был синтезирован путем химического парофазного осаждения (CVD) в 2009 году [13]. Позднее были предложены и другие способы его получения, например, дуговой разряд [14] или пиролиз графена, функционализированного азотосодержащими группами [15]. Было показано, что азот может встраиваться в решетку графена, связываясь с тремя соседними атомами углерода, или образовывать более сложные дефекты (пиридинового или пирролического типа), приводящие к формированию " отверстий" в графеновом листе [13].…”
Section: Introductionunclassified
“…Since Jasinski first reported that non-precious metal catalysts (NPMC) were obtained by pyrolysis of transition metals, carbon and nitrogen precursors at high temperature [5], massive efforts are aimed at developing NPMC to rival Pt-based catalysts. Recently, non-metal heteroatom (B, N, F, P or S)-doped carbon materials such as graphene [6][7][8][9][10][11][12], carbon nanotubes [13,14], carbon spheres [15], graphene array [16], mesoporous carbon [17] have been considered high activity for ORR. In particular, compared to other hetero atoms (B, N, P, S), F atom with high electro-negativity can easily embed in carbon blacks and form new active sites.…”
Section: Introductionmentioning
confidence: 99%